XRCC2 Arg188His polymorphism and colorectal cancer risk: a meta-analysis. Issue 10 (October 2021) - Wang, Zhiyu; Wei, Yaning; An, Lin; Xi, Chenglin; Wang, Kunjie; Hong, Dan; Shi, Yan; Zang, Aiming; Su, Shenyong; Li, Wenwen
Objective: To investigate the potential correlation between the Arg188His (rs3218536) polymorphism of X-ray repair cross-complementing 2 ( XRCC2 ) and colorectal cancer (CRC) risk, as the association remains unclear. Methods: The CNKI, PubMed, EMBASE and Cochrane library databases were systematically searched for relevant studies published up to July 2021. Data were extracted from included studies, and analysed for pooled or subgroup odds ratios (ORs) with 95% confidence intervals (CIs) using STATA 12.0 software. Results: Seven published studies were included. Pooled analysis revealed that the XRCC2 Arg188His polymorphism was associated with increased CRC risk (His versus Arg: OR 1.14, 95% CI 1.01, 1.29). Trial Sequential Analysis to test the power of the results showed that they were unreliable and the meta-analysis required additional studies. Conclusion: The current meta-analysis suggests that the XRCC2 Arg188His polymorphism may be a risk factor for CRC.